Small-Animal X-ray Dose from Micro-CT - John M. Boone; Orlando Velazquez; Simon R. Cherry (Molecular Imaging)
The use of micro-CT in small animals has increased in recent years. Although the radiation levels used for micro-CT are generally not lethal to the animal, they are high enough where changes in the immune response and other biological pathways may alter the experimental outcomes. Therefore, it is important to understand what the doses are for a specific imaging procedure. Monte Carlo simulation was used to evaluate the radiation dose to small animals (5–40 mm in diameter) as a result of X-ray exposure. Both monoenergetic (6–100 keV) and polyenergetic (15–100 kVp) X-ray sources were simulated under typical mouse imaging geometries. X-ray spectral measurements were performed on a mouse imaging X-ray system using a commercially available X-ray spectrometer, and spectra from high-energy systems were used as well. For a typical X-ray system with 1.0 mm of added Al at 40 kVp, the dose coefficients (dose to mouse per air kerma at isocenter) were 0.80, 0.63, 0.52, and 0.44 mGy/mGy for mouse diameters of 10, 20, 30, and 40 mm, respectively. A number of tables and figures are provided for dose estimation over a range of mouse imaging geometries.